Enhancing Chinese Character Mastery: The Role of Digital Apps in Teaching Stroke Order to Foreign Language Learners - Annisa Syauqina Kadar; Muthia Mutmainnah Darmuh; Jusriana Sartika Sumule; Winda Ayu Utami Rhamadanty (Jurnal MediaTIK, 2024)
Learning Chinese characters, a fundamental aspect of mastering the Chinese language, presents unique challenges due to its logographic nature and the critical importance of stroke order. Traditional methods of teaching stroke order, often through repetitive writing drills, can be monotonous and less engaging. This study explores the effectiveness of digital applications in teaching stroke order to Chinese-as-a-Foreign Language (CFL) learners, specifically focusing on the "Learning Program for Stroke Order of Chinese Characters" developed by Taiwan's Ministry of Education (MOE). Utilizing a mixed-methods research design, 17 university students with proficiency levels comparable to Hanyu Shuiping Kaoshi (HSK) 1 were assessed through semi-structured interviews, focus groups, surveys, and assessments. Quantitative findings revealed significant improvements in stroke order accuracy, with average accuracy rising from 40% to 85% after a semester of using the digital apps and retention rates remaining high at 80% three months post-intervention. Qualitative data indicated high engagement and perceived benefits from the apps' interactive features, though challenges such as technical issues and user interface difficulties were noted. The study underscores the potential of digital apps to enhance Chinese character learning through increased engagement and effective practice. It suggests that integrating these tools with traditional methods can cater to diverse learning preferences, improving overall language proficiency. Future research should address the limitations of the current study, including the small sample size and short duration, to provide a more comprehensive understanding of the long-term impacts and broader applications of digital learning tools in language education.